Desenvolvimento de técnica de cultivo para produção de células tumorais em forma de agregados em biorreator de vórtices de Taylor - Katayama, Eric Takashi (2017)
Cultivation of animal cell is gaining great interest in various biotechnological applications. The growth of cancer cells in particular has been used for cancer -fighting drugs tests. The major obstacle faced in the present is that of the drugs that have a good effectiveness in cultured cells, few have the same result in clinical trials. Antitumor drugs are tested in cells that are grown in two dimensions (2D), whereas tumor cells in organisms grow in three dimensions (3D). For this reason, there is a need to establish a methodology for cultivation of cells in 3D, like in spheroids model, because in these cells mimic the tumors in vivo. Several methodologies for production of spheroids are being searched, and the dynamic model, which is usually held in bioreactors, presents the advantage of producing a large amount of spheroids. A big drawback of using bioreactors is the agitation required to maintain homogeneous environment can be lethal to cells. To work around this problem, different types of bioreactors have been researched, and the Taylor vortices bioreactor, characterized by low shear stresses generate. As a supporting feature to reduce cell death to improve cellular aggregation, the viscosity of the culture can be increase by the use of inert additives such as dextran. The aim of this work is to identify important factors to reduce the lethal effects of agitation and facilitate the formation of spheroids using a bioreactor of Taylor and increase the viscosity of the medium with dextran use. Using a bioreactor of Taylor of 100 mL were made eight experiments of tumor RT4 lineage of bladder cancer using two methods of agitation. For each agitation methodology, four cultures were used at two stirring levels and two viscosity levels in McCoy’s medium at 37 ºc and pH around 7.20. In all these cultures, it was possible to obtain spheroids, however the culture of 90 rpm, 0,80 cp and intermittent agitation was the only in which was obtained spheroids with a mean diameter in the range of 300 to 400 μm were obtained, there were few spheroids produced. In most cultures spheroids were obtained in the range of 100 to 200 μm and with circularity values close to 0.80. In general, crops with higher viscosity provided better aggregation results. It was possible to use the aggregation model of Smoluchowski to show the aggregation formation kinetic from RT4 cells in the BVT .